Escapism, family and friends, and social interactions: How watching esports increases gaming and in-game purchase intentions - Irfan Nabil Huda; Imam Salehudin (Jurnal Manajemen dan Pemasaran Jasa, 2024)
The esports industry is experiencing rapid growth, particularly in emerging countries like Indonesia, prompting intense competition among game developers and esports event organizers to enhance the customer experience. This study aims to investigate the factors influencing watching intention, gaming intention, and in-game purchase intention, as well as examine the interrelationships among these variables. Data were collected from 243 respondents through purposive sampling, all of whom have been playing Mobile Legends for over a year, have watched the M3 World Championship eSports match, and have made at least one in-game purchase. The research hypotheses were tested using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The findings reveal that escapism, family and friends, and social interaction positively influence watching intention. Similarly, social interaction and hedonic motivation exhibit a positive effect on gaming intention. Notably, gaming intention serves as a full mediator in the relationship between watching intention and in-game purchase intention. This study contributes to the existing literature by shedding light on how Sports Consumption Motivation not only influences eSports spectators' watching intention but also gaming and in-game purchase intention. It also identifies novel factors, such as social interaction and hedonic motivation, that significantly impact gaming intention. Understanding the factors driving watching, gaming, and in-game purchase intentions enables tailored approaches that prioritize aspects like escapism, social interaction, and hedonic motivation, ultimately informing strategic decision-making and marketing efforts within the eSports industry. These findings inform future research and refine strategies for engaging with eSports audiences, benefiting both academia and industry stakeholders.